An Investigation on The Cause of Incidents Related to Scaffolding for Industrial Structure at Construction Company Located in Johor - Wan Suhaimi, Wan NurHanim; Dr Zuritah Binti A. Kadir ,; Mohd Zahruddin Bin Ruskam, (Progress in Engineering Application and Technology, 2023)
Scaffolding can be considered as one of the main contributions of accident in construction area. This research has been conducted to determine the causes of incidents involving scaffolding erection at construction company located in Johor. The objective for this study is to investigate the causes of incidents involving scaffolding erection at construction sites, to measure the level of knowledge, attitude and practice by using scaffolding awareness among employers and employees that were working at construction sites and the last objective was to propose control measure on several steps of improvement in complying with scaffolding erection at construction sites. In order to investigate the causes of incidents involving scaffolding at construction site, the data collected by referring project monthly report that focused on non-compliance and findings involving scaffolding at construction sites. In addition, to measure level of knowledge, attitude and practice, a survey questionnaire was constructed and total of 52 respondents were collected. It was found that level of knowledge, attitude and practice of employers and employees involving scaffolding awareness were high. Furthermore, to check either this knowledge, attitude and practice have a good relationship between scaffolding awareness, a hypothesis testing was conducted to determine whether a statistical association exists between two variables. It was figure out that there is significant correlation of knowledge and practices toward scaffolding awareness. Based on the result, some control measure on several steps of improvement in complying with scaffolding erection was proposed. This study can become the reference model for future investigation on the scaffolding activity at construction site or even other industries.